Pengaruh Monoklonal Antibodi Bovine Zona Pelusida 3 (bZP3) terhadap Diameter dan Atresia Folikel Ovarium Mencit (Mus musculus) - Trissatharra, Annisa; Dwiningsih, Sri Ratna; Munir, Ratna Sofaria (Majalah Obstetri & Ginekologi, 2018)
Objectives: To identify the effect of monoclonal antibody bZP3 at ovarian follicles that undergo atresia and diameter of various ovarian follicles. Materials and Methods: This is a true experimental research with post only control group design. Samples were 36 female mices (Mus musculus) which is divided into 6 groups, there are 3 control groups (group 1, 2, and 3) injected by Phospatase Buffer Saline (PBS) 50µl and 3 treatment groups (group 4, 5, and 6) injected by Mab bZP3 50µl. Group 1 and 4 terminated at 5th day, group 2 and 5 terminated at 10th day, and group 3 and 6 terminated at 20th day. Evaluation of atretic ovarian follicles and diameter of ovarian follicles performed by hematoxylin eosin (HE) and the data processed by parametric statistic. Results: There are no significant in different among groups in the aspect of atretic follicles and diameter of folicles (p>0.05), but descriptively, number of follicles undergo atresia of the follicle primary, secondary, and tertiary treatment group was higher than the control group, except on the 20th day of observation time. Conclusion: administration of Mab bZP3 had no effect to amount of atretic follicles and diameter of folicles during observation time.